2016
DOI: 10.1093/jat/bkw069
|View full text |Cite
|
Sign up to set email alerts
|

Loperamide-Related Deaths in North Carolina

Abstract: Loperamide (Imodium) has been accepted as a safe, effective, over-the-counter anti-diarrheal drug with low potential for abuse. It is a synthetic opioid that lacks central nervous system activity at prescribed doses, rendering it ineffective for abuse. Since 2012, however, the North Carolina Office of the Chief Medical Examiner has seen cases involving loperamide at supratherapeutic levels that indicate abuse. The recommended dose associated with loperamide should not exceed 16 mg per day, although users seeki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…While loperamide has been used safely for many years, there has been a recent increase in the number of loperamide overdoses and fatalities (Bishop-Freeman et al , 2016). The increase in loperamide overdoses parallels the rise in the use and abuse of prescription opiate pain medications and the related resurgence in heroin addiction (Daniulaityte et al , 2013).…”
Section: Drugs Acting At Opioid Receptors In the Gastrointestinal Tractmentioning
confidence: 99%
“…While loperamide has been used safely for many years, there has been a recent increase in the number of loperamide overdoses and fatalities (Bishop-Freeman et al , 2016). The increase in loperamide overdoses parallels the rise in the use and abuse of prescription opiate pain medications and the related resurgence in heroin addiction (Daniulaityte et al , 2013).…”
Section: Drugs Acting At Opioid Receptors In the Gastrointestinal Tractmentioning
confidence: 99%
“…It has been reported that the chronic consumption of kratom is associated with adverse reactions such as liver failure, hallucinations, and respiratory disorders. Additionally, there are several clinical reports of patient deaths linked with the intake of large doses of kratom (Bishop‐Freeman et al, ; Galbis‐Reig, ; McIntyre et al, ). On the basis of these reports, the United States Food and Drug Administration has placed an import alert on herbal supplements and dietary ingredients that contain M. speciosa (http://www.accessdata.fda.gov/cms_ia/importalert_1137.html).…”
Section: Introductionmentioning
confidence: 99%
“…In almost all of these cases, there were other drugs or substances used concomitantly. The reports did not specify whether the deaths were cardiovascular, respiratory, or neurological in nature …”
Section: Loperamide Adverse Eventsmentioning
confidence: 99%